Dishonesty Is Linked with the Spread of Infectious Diseases - Christina A. Martini; Björn Bos; Moritz A. Drupp; Jasper N. Meya; Martin F. Quaas (CESifo GmbH, 2024)
This paper investigates the link between dishonesty and the spread of COVID- 19 infections. In an online experiment and panel survey, 2,723 Germans completed an incentivized coin-tossing task in March 2020 and reported their infection status in four subsequent survey waves up until December 2021. We find that individuals who are most likely dishonest in the coin-tossing task at the onset of the pandemic, as they report the highest number of winning coin tosses, are more than twice as likely to get a future COVID-19 infection than the sample mean. Respondents who are most likely to have reported dishonestly also engage more in behaviors that increase the risk of becoming infected and of transmitting the infection relative to likely honest respondents. Hence, we postulate that differences in preferences and norm compliance are underlying determinants that affect behavior in the experiment and in the field. We observe a similar relationship at the country level between an incentivized measure of civic honesty and excess deaths due to COVID-19 in 22 OECD countries.
Keywords: C90; I12; 330; dishonesty; Covid-19 infections; excess deaths; online experiment